1996
DOI: 10.1021/jo961086a
|View full text |Cite
|
Sign up to set email alerts
|

The Synthesis of Phosphonate Ester Containing Fluorinated Vinyl Ethers

Abstract: Three novel perfluorovinyl ethers containing phosphonate ester groups, diethyl 1,1,2,2,3,3,5,6,6-nonafluoro-4-oxa-5-hexenylphosphonate, (EtO)(2)P(O)(CF(2))(3)OCF=CF(2) (1), diethyl 1,1,2,2,4,5,5-heptafluoro-3-oxa-4-pentenylphosphonate, (EtO)(2)P(O)(CF(2))(2)OCF=CF(2) (2), and diethyl 1,1,2,2,4,5,5,7,8,8-decafluoro-4-trifluoromethyl-3,6-dioxa-7-octenylphosphonate, CF(2)=CFOCF(2)CF(CF(3))O(CF(2))(2)P(O)(OEt)(2) (3), have been synthesized. Perfluorovinyl ethers 1 and 2 were synthesized from methyl 4-trifluoroethe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
1

Year Published

1997
1997
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 9 publications
0
10
1
Order By: Relevance
“…Both our experiments and literature data [12,18] do not distinguish between a mechanism where the homolysis of the sp 2 hybridized CO Á Á Á I bond is concerted with CO elimination and formation of the sp 3 hybridized CF Á Á Á I bond and a radical mechanism with an R f -OCF 2 intermediate. Fig.…”
Section: Synthesis Of Z-pfpe Diiodides Versus B-eliminationcontrasting
confidence: 66%
See 2 more Smart Citations
“…Both our experiments and literature data [12,18] do not distinguish between a mechanism where the homolysis of the sp 2 hybridized CO Á Á Á I bond is concerted with CO elimination and formation of the sp 3 hybridized CF Á Á Á I bond and a radical mechanism with an R f -OCF 2 intermediate. Fig.…”
Section: Synthesis Of Z-pfpe Diiodides Versus B-eliminationcontrasting
confidence: 66%
“…A particularly interesting synthesis of diiodides involves the transformation of acyl halides (fluorides, chlorides and bromides) in acyl iodides employing KI or LiI in aprotic solvents followed by a thermal or photolytic extrusion of CO in the presence of I 2 . This reaction has been reported starting either from perfluoroalkyl halides [11,[12][13][14] or from PFPEs with -OCF 2 CF 2 COF or -OCF(CF 3 )COF end groups [15] but never from terminal -OCF 2 COX (X = F, Cl). It has been postulated that the fundamental step of the reaction, the extrusion of CO, has radical character [12,13].…”
Section: Introductionmentioning
confidence: 90%
See 1 more Smart Citation
“…25 Quantum mechanical calculations have been undertaken in an investigation of the mechanisms of proton transfer (i.e. proton hopping) in neat phosphoric acid, 30,31 liquid PA, 32 and heptyl PA. 33 Diverse phosphonic acid functional polymers have received significant interest as intrinsically conducting membrane materials, including perfluorovinylethers, 34,35 polytrifluorostyrenes, 36,37 polyphenylsulfones, 38,39 polyphosphazenes, 40,41 and other grafted copolymers. 34 Several synthetic approaches have also been implemented to assess various PAs.…”
Section: Introductionmentioning
confidence: 99%
“…To overcome this problem, the mixture of phosphonate, monophosphonic acid, and phosphonic acid was reacted with phosphorus pentachloride to produce various phosphoryl chlorides, but in low overall yield. Pedersen et al 39 demonstrated that the deprotection of the trifluorovinyl ether moiety prior to its oxidation prevents the dealkylation of the phosphonate (Scheme 2). Initially, the deprotection of the double bond occurs, followed by oxidation of the phosphonate, thus avoiding the dealkylation of the phosphonate group, which allows the synthesis of perfluorinated diethyl phosphonate in good yields (69% based on the starting iodide), avoiding the isolation of the troublesome phosphoryl chlorides.…”
Section: Monomer Synthesismentioning
confidence: 99%